Study ABO/Rh system with Endothelial Inflammatory Factors in Iraqi Arab Female with Diabetes Mellitus Type II - Baghdad Science Journal (مجلة بغداد للعلوم)
Diabetes mellitus type II is a disorder of metabolism and complex diseases affected by genetic environmental factors and associated with inflammation. The symptoms of type II diabetes develop gradually, which are associated with increased blood concentration of marker of the endothelial inflammatory factors. The expression of adhesion molecules, including E-selectin, intracellular adhesion molecule-1(ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) on the surface of vascular endothelial cells to help leukocyte stick to other surrounding tissues. Many researchers have made attempts to determine the significance of particular ABO phenotype for the susceptibility to diseases. Many reports show a strong association with the ABO blood groups and diabetes Type II. Dysfunction increases risk of type II diabetes among women with low level of subclinical incident diabetes. For that reason the present study has been designed to study the association between diabetic, endothelial dysfunction and blood group in Iraqi Arab diabetic women. Sixty patients of Iraqi Arabs female with previous diagnosed diabetic type II involved in this study and comparison with twenty controls matched in age, sex and ethnic groups. Both of patients and control divided into four sub groups according to the blood types. We evaluated endothelial inflammatory factors ICAM, VCAM and E-Selectin. Present data showed a significant difference in the serum level of ICAM-1 and E-section between diabetes mellitus type II patients and controls while there were no significant differences in the serum level of VCAM-1. In conclusion, significant increasing of the level of ICAM-1 and E-selectin made them as a risk factors to predict diabetes progression, women who carry blood group A, B and AB show appositive association with diabetic, while females who carry blood group O less susceptible to infected with diabetes mellitus type II.